Three years follow-up of a large cyst: A case report - Chadi TORBAY; Valérie BATROUNI (International Arab Journal of Dentistry (IAJD), 2020)
The main goal of root canal therapy is to eliminate the pathogenic effects of bacteria from the root canal system and that through chemomechanicaldebridement followed by inert root filling to prevent microorganisms from infecting or reinfecting root canals and the periradicular tissues.Defining clinical healing of apical periodontitis after endodontic treatment is very difficult especially finding a relevant radiologic examination method for accurate observation. Therefore, various radiologic techniques were used among which we site the periapical x-rays, the orthopantomogram, the cone beam computed tomography, and that depending on the size and the localization of the pathological entity.The aim of the present paper was to show the treatment outcome and the healing of large periapical radiolucency controlled with CBCT.